PENGEMBANGAN SISTEM INFORMASIALUMNI MAHASISWA UNIVERSITAS SELAMAT SRIBERBASIS WEB - adminjfik adminjfik; Febriyanti Darnis Mila; Riky Dwi Darmawan Mila (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2022)
In this study, authors designed and built web based alumni information systems websites as a means for alumni to know information about alumni.The study was instrumental in assisting in the process of alumni management of the data, the authors found that the alumni findings had been using less-than-optimal spreadsheets. The method used in this study uses the prototype method, a system of life cycles based on working models, the goal is to develop models into final systems. That means the system will be developed faster than traditional methods and its costs will be lower. The result of this study is the web based alumni information system website. In the information system lies a feat, which shows the data of successful alumni so that users can look at successful alumni.